Analýza možnosti užití III. a IV. generace jaderných reaktorů v ČR - Gajdzica, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Diplomová práce se zabývá analýzou možností užití jaderných reaktorů III. a IV. generace v České republice. Úvodní část se zabývá základními principy jaderné energetiky a palivovým cyklem, který s problematikou úzce souvisí a jeho vývoj a aplikace v praxi bude mít významný vliv jak na výběr budoucích typů jaderných reaktorů IV. generace, tak na otázku vypořádání se s použitým jaderným palivem. V dalších částech se diplomová práce zabývá současným stavem jaderné energetiky v České republice, porovnává konkrétní vybrané typy jaderných elektráren III. generace a obecně popisuje jaderné reaktory a elektrárny IV. generace. Závěrečná část práce se zaměřuje na otázky týkající se možnosti výstavby nových bloků jaderných elektráren v České republice a uvádí konkrétní doporučení z pohledu autora.

The thesis deals with the analysis of possibilities for use of III. and IV. generation of nuclear reactors for the Czech Republic. Introduction deals with basic principles of nuclear energetics and fuel cycle which is closely associated with the issue and its development and application in practice will have a significant effect both for choice of future types of nuclear reactors of IV. generation and the matter of settlement with spent nuclear fuel. In other parts the thesis deals with the present state of nuclear energetics in the Czech Republic, compares concrete chosen types of nuclear power plants of III. generation and generally describes nuclear reactors and power plants of IV. generation. Final part of the work is focused on questions concerning the possibility of construction of new blocks of nuclear power plants in the Czech Republic and presents concrete recommendation from author´s point of view.
Analysis of possibilities for use of III. and IV. generation of nuclear reactors for the Czech Republic
Keywords: Jaderné elektrárny; jaderné reaktory; jaderné palivo; palivový cyklus; instalovaný výkon; průmysl; elektrická energie; generace; Nuclear power plants; nuclear reactors; nuclear fuel; fuel cycle; installed power; industry; electrical energy; generation